5.2.38 Problems 3701 to 3800

Table 5.243: Second order linear ODE

#

ODE

Mathematica

Maple

13408

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 0 \]

13409

\[ {}4 y^{\prime \prime }-12 y^{\prime }+5 y = 0 \]

13410

\[ {}3 y^{\prime \prime }-14 y^{\prime }-5 y = 0 \]

13413

\[ {}y^{\prime \prime }-8 y^{\prime }+16 y = 0 \]

13414

\[ {}4 y^{\prime \prime }+4 y^{\prime }+y = 0 \]

13415

\[ {}y^{\prime \prime }-4 y^{\prime }+13 y = 0 \]

13416

\[ {}y^{\prime \prime }+6 y^{\prime }+25 y = 0 \]

13417

\[ {}y^{\prime \prime }+9 y = 0 \]

13418

\[ {}4 y^{\prime \prime }+y = 0 \]

13431

\[ {}y^{\prime \prime }-y^{\prime }-12 y = 0 \]

13432

\[ {}y^{\prime \prime }+7 y^{\prime }+10 y = 0 \]

13433

\[ {}y^{\prime \prime }-6 y^{\prime }+8 y = 0 \]

13434

\[ {}3 y^{\prime \prime }+4 y^{\prime }-4 y = 0 \]

13435

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

13436

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

13437

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 0 \]

13438

\[ {}9 y^{\prime \prime }-6 y^{\prime }+y = 0 \]

13439

\[ {}y^{\prime \prime }-4 y^{\prime }+29 y = 0 \]

13440

\[ {}y^{\prime \prime }+6 y^{\prime }+58 y = 0 \]

13441

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = 0 \]

13442

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]

13443

\[ {}9 y^{\prime \prime }+6 y^{\prime }+5 y = 0 \]

13444

\[ {}4 y^{\prime \prime }+4 y^{\prime }+37 y = 0 \]

13451

\[ {}y^{\prime \prime }-3 y^{\prime }+8 y = 4 x^{2} \]

13452

\[ {}y^{\prime \prime }-2 y^{\prime }-8 y = 4 \,{\mathrm e}^{2 x}-21 \,{\mathrm e}^{-3 x} \]

13453

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 6 \sin \left (2 x \right )+7 \cos \left (2 x \right ) \]

13454

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 10 \sin \left (4 x \right ) \]

13455

\[ {}y^{\prime \prime }+2 y^{\prime }+4 y = \cos \left (4 x \right ) \]

13456

\[ {}y^{\prime \prime }-3 y^{\prime }-4 y = 16 x -12 \,{\mathrm e}^{2 x} \]

13457

\[ {}y^{\prime \prime }+6 y^{\prime }+5 y = 2 \,{\mathrm e}^{x}+10 \,{\mathrm e}^{5 x} \]

13458

\[ {}y^{\prime \prime }+2 y^{\prime }+10 y = 5 x \,{\mathrm e}^{-2 x} \]

13463

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 10 \,{\mathrm e}^{2 x}-18 \,{\mathrm e}^{3 x}-6 x -11 \]

13464

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 6 \,{\mathrm e}^{-2 x}+3 \,{\mathrm e}^{x}-4 x^{2} \]

13471

\[ {}y^{\prime \prime }+y = x \sin \left (x \right ) \]

13472

\[ {}y^{\prime \prime }+4 y = 12 x^{2}-16 x \cos \left (2 x \right ) \]

13475

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = 9 x^{2}+4 \]

13476

\[ {}y^{\prime \prime }+5 y^{\prime }+4 y = 16 x +20 \,{\mathrm e}^{x} \]

13477

\[ {}y^{\prime \prime }-8 y^{\prime }+15 y = 9 \,{\mathrm e}^{2 x} x \]

13478

\[ {}y^{\prime \prime }+7 y^{\prime }+10 y = 4 x \,{\mathrm e}^{-3 x} \]

13479

\[ {}y^{\prime \prime }+8 y^{\prime }+16 y = 8 \,{\mathrm e}^{-2 x} \]

13480

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 27 \,{\mathrm e}^{-6 x} \]

13481

\[ {}y^{\prime \prime }+4 y^{\prime }+13 y = 18 \,{\mathrm e}^{-2 x} \]

13482

\[ {}y^{\prime \prime }-10 y^{\prime }+29 y = 8 \,{\mathrm e}^{5 x} \]

13483

\[ {}y^{\prime \prime }-4 y^{\prime }+13 y = 8 \sin \left (3 x \right ) \]

13484

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 8 \,{\mathrm e}^{2 x}-5 \,{\mathrm e}^{3 x} \]

13485

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 2 \,{\mathrm e}^{2 x} x +6 \,{\mathrm e}^{x} \]

13486

\[ {}y^{\prime \prime }-y = 3 \,{\mathrm e}^{x} x^{2} \]

13487

\[ {}y^{\prime \prime }+y = 3 x^{2}-4 \sin \left (x \right ) \]

13488

\[ {}y^{\prime \prime }+4 y = 8 \sin \left (2 x \right ) \]

13491

\[ {}y^{\prime \prime }-6 y^{\prime }+8 y = x^{3}+x +{\mathrm e}^{-2 x} \]

13492

\[ {}y^{\prime \prime }+9 y = {\mathrm e}^{3 x}+{\mathrm e}^{-3 x}+{\mathrm e}^{3 x} \sin \left (3 x \right ) \]

13493

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = {\mathrm e}^{-2 x} \left (1+\cos \left (x \right )\right ) \]

13494

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = x^{4} {\mathrm e}^{x}+x^{3} {\mathrm e}^{2 x}+x^{2} {\mathrm e}^{3 x} \]

13495

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = x \,{\mathrm e}^{-3 x} \sin \left (2 x \right )+x^{2} {\mathrm e}^{-2 x} \sin \left (3 x \right ) \]

13505

\[ {}y^{\prime \prime }+y = \cot \left (x \right ) \]

13506

\[ {}y^{\prime \prime }+y = \tan \left (x \right )^{2} \]

13507

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

13508

\[ {}y^{\prime \prime }+y = \sec \left (x \right )^{3} \]

13509

\[ {}y^{\prime \prime }+4 y = \sec \left (x \right )^{2} \]

13510

\[ {}y^{\prime \prime }+y = \tan \left (x \right ) \sec \left (x \right ) \]

13511

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = {\mathrm e}^{-2 x} \sec \left (x \right ) \]

13512

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = {\mathrm e}^{x} \tan \left (2 x \right ) \]

13513

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = \frac {{\mathrm e}^{-3 x}}{x^{3}} \]

13514

\[ {}y^{\prime \prime }-2 y^{\prime }+y = x \,{\mathrm e}^{x} \ln \left (x \right ) \]

13515

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \csc \left (x \right ) \]

13516

\[ {}y^{\prime \prime }+y = \tan \left (x \right )^{3} \]

13517

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \frac {1}{1+{\mathrm e}^{x}} \]

13518

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \frac {1}{1+{\mathrm e}^{2 x}} \]

13519

\[ {}y^{\prime \prime }+y = \frac {1}{\sin \left (x \right )+1} \]

13520

\[ {}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{x} \arcsin \left (x \right ) \]

13521

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \frac {{\mathrm e}^{-x}}{x} \]

13522

\[ {}y^{\prime \prime }-2 y^{\prime }+y = x \ln \left (x \right ) \]

13523

\[ {}x^{2} y^{\prime \prime }-6 x y^{\prime }+10 y = 3 x^{4}+6 x^{3} \]

13524

\[ {}\left (1+x \right )^{2} y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }+2 y = 1 \]

13525

\[ {}\left (x^{2}+2 x \right ) y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }+2 y = \left (x +2\right )^{2} \]

13526

\[ {}x^{2} y^{\prime \prime }-x \left (x +2\right ) y^{\prime }+\left (x +2\right ) y = x^{3} \]

13527

\[ {}x \left (x -2\right ) y^{\prime \prime }-\left (x^{2}-2\right ) y^{\prime }+2 \left (x -1\right ) y = 3 x^{2} \left (x -2\right )^{2} {\mathrm e}^{x} \]

13528

\[ {}\left (2 x +1\right ) \left (1+x \right ) y^{\prime \prime }+2 x y^{\prime }-2 y = \left (2 x +1\right )^{2} \]

13529

\[ {}\sin \left (x \right )^{2} y^{\prime \prime }-2 \sin \left (x \right ) \cos \left (x \right ) y^{\prime }+\left (\cos \left (x \right )^{2}+1\right ) y = \sin \left (x \right )^{3} \]

13531

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+3 y = 0 \]

13532

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

13533

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+3 y = 0 \]

13534

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 0 \]

13535

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = 0 \]

13536

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+13 y = 0 \]

13537

\[ {}3 x^{2} y^{\prime \prime }-4 x y^{\prime }+2 y = 0 \]

13538

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+9 y = 0 \]

13539

\[ {}9 x^{2} y^{\prime \prime }+3 x y^{\prime }+y = 0 \]

13540

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+10 y = 0 \]

13544

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 4 x -6 \]

13545

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+8 y = 2 x^{3} \]

13546

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+2 y = 4 \ln \left (x \right ) \]

13547

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = 2 x \ln \left (x \right ) \]

13548

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = 4 \sin \left (\ln \left (x \right )\right ) \]

13550

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }-10 y = 0 \]

13551

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

13552

\[ {}x^{2} y^{\prime \prime }+5 x y^{\prime }+3 y = 0 \]

13553

\[ {}x^{2} y^{\prime \prime }-2 y = 4 x -8 \]

13554

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+4 y = -6 x^{3}+4 x^{2} \]

13555

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-6 y = 10 x^{2} \]